Bilayer cryogel wound dressing and skin regeneration grafts for the treatment of acute skinwounds - Priya, S. Geetha; Gupta, Ankur; Jain, Era; Sarkar, Joyita; Damania, Apeksha; Jagdale, Pankaj R.; Chaudhari, Bhushan P.; Gupta, Kailash C.; Kumar, Ashok (ACS Applied Materials & Interfaces, 2016)
In this study, the potential of cryogel bilayer wound dressing and skin regenerating graft for the treatment of surgically created full thickness wounds was evaluated. The top layer was composed of polyvinylpyrrolidone-iodine (PVP-I) and served as the antiseptic layer, while the bottom regenerative layer was made using gelatin cryogel. Both components of the bilayer showed typical features of a cryogel interconnected macropore network, rapid swelling, high water uptake capacity of about 90%. Both PVP and gelatin cryogel showed high tensile strength of 45 and 10 kPa, respectively. Gelatin cryogel sheets were essentially elastic and could be stretched without any visible deformation. The antiseptic PVP-I layer cryogel sheet showed sustained iodine release and suppressed microbial growth when tested with skin pathogens (zone of inhibition cm for sheet of 0.9 cm diameter). The gelatin cryogel sheet degraded in vitro in weeks. The gelatin cryogel sheet supported cell infiltration, attachment, and proliferation of fibroblasts and keratinocytes. Microparticles loaded with bioactive molecules (mannose-6-phosphate and human fibrinogen) were also incorporated in the gelatin cryogel sheets for their role in enhancing skin regeneration and scar free wound healing. In vivo evaluation of healing capacity of the bilayer cryogel was checked in rabbits by creating full thickness wound, defect (diameter 2 cm). Macroscopic and microscopic observation at regular time intervals for 4 weeks demonstrated better and faster skin regeneration in the wound treated with cryogel bilayer as compared to untreated defect and the repair was comparable to commercial skin regeneration scaffold Neuskin-F. Complete skin regeneration was observed after 4 weeks' of implantation with no sign of inflammatory response. Defects implanted with cryogel having mannose-6-phosphate showed no scar formation,, while the wound treated with bilayer incorporated with human fibrinogen microparticles showed early signs of skin regeneration; epidermis formation occurred at 2 weeks after implantation.